Community Conserved Areas in North East India: some Observations in Assam, Meghalaya and Arunachal Pradesh - Chatterjee, Sudipto; Ghosh, Sonali; Sarma, Jayanta; Barik, S. K.; Tewari, B. K.; Das, Kulen Chandra (Indian Forester, 2011)
Community Conserved Areas (CCAs) are a category of forests where communities have a stake or ownership and are increasingly getting recognized global recognition. CCAs across the globe are now being documented fortheir biological values, management regimes and conservation significance. Case studies were conducted in three states in North East India to document some of the CCAs in the region.